VD_FINDINFO HC / 2014 / 871 vom 9. Oktober 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES | 105 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)